Vitamin D Ameliorates Impaired Wound Healing in Streptozotocin-Induced Diabetic Mice by Suppressing Endoplasmic Reticulum Stress - Yi Feng Yuan; Sushant K. Das; Mao Quan Li (Journal of Diabetes Research)
Background. This study is designed to investigate whether vitamin D promotes diabetic wound healing and explore the potential mechanism which may be involved in the healing process. Material and Methods. Human umbilical vein endothelial cells (HUVECs) were treated with 200 μg/ml of advanced glycation end product-modified human serum albumin (AGE-HSA) and 250 mg/dl of glucose with vitamin D. Cell viability was analyzed using the CCK-8 assay, and the apoptosis rate was measured using flow cytometry. Endogenous markers of ER stress were quantified using Western blot and a real-time polymerase chain reaction. Diabetic mice were treated with vitamin D (100 ng/kg per day) for 14 days. The ulcer area and ulcerative histology were detected dynamically. Results. Vitamin D administration not only decreased the apoptosis rate but also increased cell viability. Furthermore, the expression of endogenous markers of ER stress was downregulated as a result of vitamin D treatment. Vitamin D supplementation significantly accelerated wound healing of diabetic mice and improved the healing quality. Further studies showed that reduced ER stress was associated with the positive outcome. Conclusion. These results suggest that vitamin D may ameliorate impaired wound healing in diabetic mice by suppressing ER stress.